The role of construction companies in modern housing: Precol’s footprint in late colonial Angola - Rodrigues, I. (Proceedings 17th International Docomomo Conference, 2022)
This article reflects on Angola’s modern heritage and discusses its relevance to housing research, bringing to light modern architectural projects in Sub–Saharan Africa that are little known internationally. During the Portuguese colonial period, mainly in the 1960s, Luanda was transformed into an urban laboratory of modern western architectural experimentation. In this process, the role of neighbourhood units from the city centre to the suburbs stands out, announcing a futuristic and optimistic vision for urban living. Beyond the formal expression this article also shows that Luso– Angolan architects achieved the original adaptation of modern architecture to the climate. The aim of this paper is to outline the footprint of private promotors in the construction and property development of modern dwellings in Luanda. An example is a footprint of Predial Económica Ultramarina (Precol), a company engaged in the construction and marketing of large housing complexes, such as the neighbourhood’s units of Prenda (1963) and CTT (1968), part of urban plans of public promotion launched by the urbanisation of the city of Luanda. Did the private promotors act as mediators between private contacts and state administrations? Had they influenced the choice of construction techniques and the following architectural design? These neighbourhoods, mostly of modern affiliation, represent the transversality of the Modern Movement, born in Europe and applied by Portuguese architects in other countries. Inhabited by the colonial upper–middle class, the “Precol neighbourhoods” could adapt to new living after independence. Today, they show their resilience through excellent construction techniques and architectural details, harbouring various forms of occupation. By rescripting the historical narrative of architectural modernism, highlighting the specific construction elements or systems relevant to the architectural design of dwellings, other futures may emerge as possible for new stakeholders who are committed to strategies for the renewal of modern heritage.